POTENSI DAN TANTANGAN PENGEMBANGAN WISATA AIR TERJUN DI DESA SOROPIA KABUPATEN KONAWE - Riston G. Ahmad; Cerry Triwulan Sari; Wa Ode Musdalifa; Darmanto; Ari Ferdiansah; Tri Indra Halimudin; Patta Hindi Asis (Halu Oleo University, 2024)
This study aims to analyze the potential for developing waterfall tourism in Soropia Village, Soropia District, Konawe Regency, Southeast Sulawesi Province. Soropia Village is known for its abundant natural potential, which has not yet been fully utilized, one of which is waterfall tourism. This research uses a qualitative approach with data collection techniques such as in-depth interviews, field observations, and document studies. The results show that the waterfalls in Soropia Village have great potential to be developed into a leading tourist destination that could boost the local economy and improve the welfare of the community. The natural beauty, which remains pristine and far from the crowds, makes it a unique attraction for both domestic and international tourists. If well-managed, this potential could not only enhance the tourism sector but also provide socio-economic benefits for the local community. Considering the ecosystem potential and the aesthetic value it holds, the waterfalls in Soropia Village could become an attractive natural tourism option, in line with the village's mission to utilize its natural resources to improve the community's economy. This study also recommends management strategies that involve local communities and consider environmental sustainability, ensuring that waterfall tourism development can provide long-term benefits.